2020
DOI: 10.1097/iae.0000000000002797
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Ability of Preoperative Quantitative Spectral-Domain Optical Coherence Tomography Characteristics to Predict Visual Outcome in Idiopathic Macular Hole Surgery

Abstract: Purpose: To determine which spectral domain optical coherence tomography biomarkers of idiopathic macular hole (MH) correlate with the postoperative best-corrected visual acuity (BCVA) in anatomically closed MH. Methods: Retrospective analysis of spectral domain optical coherence tomography scans of 44 patients presenting with MH followed for a mean of 17 months. Widths of MH aperture, base, and ellipsoid zone disruption were calculated from presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
9
1
Order By: Relevance
“…Minimum MH size has been reported to be a common predictor for post-MH surgery visual outcome. [15][16][17] However, the current multivariable analysis demonstrated that minimum MH size was not statistically significant for 1-year visual acuity outcome, and there were no differences in baseline visual acuity and 1-year visual acuity among different MH sizes. This unexpected finding could be attributed to the relatively small sample size.…”
Section: Discussioncontrasting
confidence: 57%
“…Minimum MH size has been reported to be a common predictor for post-MH surgery visual outcome. [15][16][17] However, the current multivariable analysis demonstrated that minimum MH size was not statistically significant for 1-year visual acuity outcome, and there were no differences in baseline visual acuity and 1-year visual acuity among different MH sizes. This unexpected finding could be attributed to the relatively small sample size.…”
Section: Discussioncontrasting
confidence: 57%
“…Mehta et al reported that preoperative FTMH hypertransmission size was associated with postoperative visual function, and it may represent a new and easy-to-visualize predictive imaging biomarker for FTMH management. 25 Because the FTMH sizes obtained with the novel proposed method and the standard method were not found to be identical, future studies will be needed to determine if this novel measurement strategy would potentially reclassify FTMH and alter the expected outcomes of treatments or if, on the contrary, the differences in the FTMH size obtained by the two methods is clinically negligible and expected outcomes of the new method are similar to the old, more labor intensive and subjective method.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in BCVA between the overall air group and the overall silicone oil group. Because some studies had shown that the improvement of visual function was closely related to both the MMHD and the closure rate of IMH [24][25] , each group was subdivided according to MMHD in our study. It was found that BCVA of MMHD1 air group was better than silicone oil group, but significant difference was not found in MMHD2 between the two tamponades.…”
Section: Discussionmentioning
confidence: 99%